Tribological and oxidational properties of porous high-pressure crystallized and vitamin E–incorporated ultra-high-molecular weight polyethylene as an artificial cartilage. (2nd July 2015) - Chou, Chau-Chang; Wang, Yang-Zhi; You, Jyun-Hao; Wu, Cheng-Lun
The material properties of porous high-pressure crystallized ultra-high-molecular weight polyethylene containing vitamin E as a plasticizing agent and an antioxidant were studied. Two porous ultra-high-molecular weight polyethylene samples, with and without vitamin E, were produced by mixing ultra-high-molecular weight polyethylene powder and sodium chloride micro particles before the high-pressure crystallized process. A solid ultra-high-molecular weight polyethylene without vitamin E additive was made as a benchmark. The porosities of both porous samples were evaluated by energy-dispersive X-ray analysis of cross-sectional areas. The crystallinity of the composites was examined by thermal (differential scanning calorimetry) and spectral (X-ray diffraction) analyses. The short-term and long-term oxidative stabilities of porous ultra-high-molecular weight polyethylenes, with or without incorporated vitamin E, were investigated, respectively, by evaluations of differential scanning calorimetry oxidation induction time and Fourier transform infrared oxidation index. The tribological performance was also studied by a pin-on-disk test under lubrication with normal saline. The particulate size distribution of wear debris demonstrated the better biocompatibility of ultra-high-molecular weight polyethylenes with higher porosity. However, the antiwear capability and the oxidation resistance of the porous ultra-high-molecular weight polyethylene were inferior to those of the solid one. These drawbacks were significantly reduced by the influence of the vitamin E agent.